Off-label uses of retinoids in dermatology - Wei Li; Ying Liu; Quan Luo; Xue-Mei Li; Xi-Bao Zhang (Our Dermatology Online, 2012)
Retinoids has been used widely in the topical and systemic treatments of various dermatoses: psoriasis, disorders of keratinization (DOK), keratotic genodermatosis, and severe acne. Moreover, it is also used in the treatment and/or chemoprevention of skin cancer and other neoplasms. Retinoids display key regulatory functions and most dermatologists are familiar with the FDA-approved indication of this medication. Retinoic acid is a potent signaling molecule that is essential for many biological processes, and its levels are tightly regulated by mechanisms that are only partially understood. This article will review these recent findings and attempt to synthesize their meaning to provide a view into the off-label uses of retinoids in dermatology with an emphasis on oral isotretinoin and acitrein.